Applications of nanobodies in brain diseases - Zheng, Fang; Pang, Yucheng; Li, Luyao; Pang, Yuxing; Zhang, Jiaxin; Wang, Xinyi; Raes, Geert (Frontiers in Immunology, 2022)
Nanobodies are antibody fragments derived from camelids, naturally endowed with properties like low molecular weight, high affinity and low immunogenicity, which contribute to their effective use as research tools, but also as diagnostic and therapeutic agents in a wide range of diseases, including brain diseases. Also, with the success of Caplacizumab, the first approved nanobody drug which was established as a first-in-class medication to treat acquired thrombotic thrombocytopenic purpura, nanobody-based therapy has received increasing attention. In the current review, we first briefly introduce the characterization and manufacturing of nanobodies. Then, we discuss the issue of crossing of the brain-blood-barrier (BBB) by nanobodies, making use of natural methods of BBB penetration, including passive diffusion, active efflux carriers (ATP-binding cassette transporters), carrier-mediated influx via solute carriers and transcytosis (including receptor-mediated transport, and adsorptive mediated transport) as well as various physical and chemical methods or even more complicated methods such as genetic methods via viral vectors to deliver nanobodies to the brain. Next, we give an extensive overview of research, diagnostic and therapeutic applications of nanobodies in brain-related diseases, with emphasis on Alzheimer’s disease, Parkinson’s disease, and brain tumors. Thanks to the advance of nanobody engineering and modification technologies, nanobodies can be linked to toxins or conjugated with radionuclides, photosensitizers and nanoparticles, according to different requirements. Finally, we provide several perspectives that may facilitate future studies and whereby the versatile nanobodies offer promising perspectives for advancing our knowledge about brain disorders, as well as hopefully yielding diagnostic and therapeutic solutions.